ALAM PERSONIFIKASI MARTABAT MANUSIA: PEMBABATAN HUTAN DI KALIMANTAN TIMUR: (Refleksi Filosofis atas Alam Dinamis dan Metaforis dalam Perspektif Armada Riyanto) - Thomas Kadek Lintang Kurniawan; Emannuel Gebi Koten; Ayub Api Bato; Fransiskus Xaverius Eko Armada Riyanto (Jurnal Reinha, 2022)
The focus of this paper is a philosophical study of Nature as the personification of a dignified human being. This study aims to provide an in-depth explanation of the similarities between nature and humans. The discussion of this paper departs from the reality of human life today, especially in East Kalimantan, which has a tendency to overexploit nature in managing nature. This reality shows that there is no ecological ethics. The purpose of this paper is to provide a solution in the form of a philosophical idea of ??how humans should treat nature. The methodology of this paper is a literature study by exploring the philosophical ideas of Armada Riyanto about Dynamic and Metaphorical Nature in his book Menjadi-Mencintai: Berfilsafat Teologis Sehari-hari. The idea is used to examine the reality of nature today. The finding in this paper is that nature is not treated well by some humans for the sake of seeking one-sided advantage. It is exactly like human dignity which is marginalized in today's social life. Therefore, humans must treat nature as themselves in order to create good, right and beautiful harmonization in their lives.